Three new species of Elaphoglossum Schott ex J. Sm. (Dryopteridaceae) from the pacific of Costa Rica - Rojas-Alvarado, Alexander Francisco; Baaijen-Harteveld, Wouter (Universidad de Málaga. Servicio de Publicaciones e Intercambio Científico, 2017)
In this paper three new species of Elaphoglossum Schott ex J. Sm., are described and illustrated, located on the pacific slope of Cordillera de Talamanca and Cerro Caraigres (Cerro Dragón), Costa Rica. The new species are: E. dragonense A. Rojas, E. flavosquamum A. Rojas and E. pacificum A. Rojas, all belong to the section Elaphoglossum subsection Pachyglossa Christ. The first species resembles E. gloeorrhizum Mickel but is separated by showing a scaly rhizome, phyllopodia with two sections, the basal one resinous as the rhizome and the second non-resinous, bigger stipe scales, and the abaxial blade is scaly. The second entity resembles E. delgadilloanum A. Rojas, but differs by having blonde to orange-yellowish rhizome scales with long lateral processes and the blade scales are mainly smaller, less dense and bicolorous with black central body and brown rays. The latter species is similar to E. cismense Rosenst., but is identified by its more slender rhizome, fronds at less distance between them, shorter phyllopodia, narrowly elliptic blade, bigger abaxial blade scales and a linear-elliptical and narrower fertile blade
Tres especies nuevas de Elaphoglossum Schott ex J. Sm. (Dryopteridaceae) para el pacífico de Costa Rica
Keywords: Biología; Caraigres; Elaphoglossum dragonense; Elaphoglossum flavosquamum; Elaphoglossum pacificum; Endemic; Neotropics; Subsection Pachyglossa; Endémico; Neotrópico; Subsección Pachyglossa